The Effectiveness of Communication in Online Learning on the Ability to Read the Qur'an - Delia Wahyu Khoirunisa; Lulu Dwi Nayla; Afridho; Syamsul Rizal; Yokha Latief Ramadhan (CV Naskah Aceh, 2026)
The development of information technology in the digital era has brought significant changes to Islamic education , particularly in the process of learning to read the Qur'an, which is now widely done online . Online Qur'an learning provides easy access and flexible time , but requires effective communication between educators and participants to achieve learning objectives optimally . This study uses a qualitative descriptive literature review , examining sources such as books , scientific journals , articles , and previous studies on the effectiveness of communication in online Qur'an learning . The analysis was conducted through an Islamic educational and learning communication approach to understand the influence of communication on participants ' Qur'an reading abilities . The results of the study indicate that effective communication between educators and participants has a positive impact on participants ' abilities in reading the Qur'an, especially in Tajweed, makharijul huruf , and reading fluency . The use of digital media such as video, audio, and interactive applications also helps make the learning process more effective and interesting . However , online learning still faces challenges such as Limited internet access and lack of direct interaction . Therefore , interactive communication , appropriate learning media , and proper guidance are needed to ensure optimal online Quran learning .